Accuracy of the serological ELISA test compared with the polymerase chain reaction for the diagnosis of cytomegalovirus infection in pregnancy - Parmigiani, Silvana Varella; Barini, Ricardo; Costa, Sandra Cecília Botelho; Amaral, Eliana; Silva, José Carlos Gama da; Silva, João Luiz de Carvalho Pinto e (São Paulo Medical Journal, 2003)
CONTEXT: The most frequently used methods for detecting antibodies are the indirect immunofluorescence test and the enzymatic immunoassay (ELISA). The polymerase chain reaction is a molecular biology technique in which the production of large amounts of specific DNA fragments is induced from very low concentrations of complex substrates aloowing the detection of very low amounts of viral particles. OBJECTIVE: To assess the accuracy of serological/ ELISA tests in comparison with the polymerase chain reaction in maternal blood to diagnose cytomegalovirus infection. DESIGN: A descriptive study was performed. SETTING: High-risk outpatient clinic of Campinas University (Unicamp). PARTICIPANTS: We selected 243 pregnant women. All of them had been indicated for blood sampling because of suspicions of cytomegalovirus infection and also because of other infections. MAIN MEASUREMENTS: The group was tested for cytomegalovirus. Serological tests were run and compared to the polymerase chain reaction, which was considered to be the gold standard. Status analyses were done using Fisher’s exact test, via the SAS software. RESULTS: The previous cytomegalovirus infection rate was 94.6%. The main reasons for inclusion in the study were fetal nervous system malformation (25.5%), maternal toxoplasmosis (25.5%) and Rh isoimmunization (14.8%). Only two women were included because of positive serological immunoglobulin M test for cytomegalovirus. The sensitivity and specificity of the serological tests were 94% and 6% for immunoglobulin G. CONCLUSION: Serological tests had lower sensitivity in comparison with the polymerase chain reaction test when diagnosing cytomegalovirus infection. The consequences of positive polymerase chain reaction and negative immunoglobulin M in women remain unknown.